TELE-OPERATED ROBOT USING VC PROGRAMMING PROTOCOL - Hasbi, Ahmad Farhan (Universiti teknologi petronas, 2007)
This project deals with a development of a tele-operated robot that utilizes I C bus as the main communication medium. The development stages are comprised of structure and mechanism construction, electronic circuit development and programming algorithms generation. The tele-operated robot functions as a transporter. It has the ability to transport objects from one location to another. This is done by the mechanism part that includes the gripper and the lifter part. The function of the gripper part is to grip or release desired objects. The lifter part on the other hand, lifts the gripped object to a desired height. This makes the tele-operated robot a versatile transportermedium that can be used in many industries such as to transport hazardous chemical waste and to place objects of interest at a shelf in hypermarkets. The communication between micro-controllers that controls the robot operation utilizes the I C bus. This bus is categorized under the serial bus. Serial bus is chosen as the maincommunication linkdueto its capability of reduces circuit complexity and eases system modifications when needed. In conclusion, the tele-operated robot is best implemented with I2C bus as the communication medium between micro-controllers that control the robot's movement but not practical for the remote control communication medium to the robot. This is due to the fact that a robot is usually controlled from a far distance where else I2C bus has alimited length ofbus. Wireless communication such as blue-tooth, infra red and web based control are better suited for this purpose.